Type I interferon promotes alveolar epithelial type II cell survival during pulmonary Streptococcus pneumoniae infection and sterile lung injury in mice. Issue 9 (12th July 2016) - Maier, Barbara B.; Hladik, Anastasiya; Lakovits, Karin; Korosec, Ana; Martins, Rui; Kral, Julia B.; Mesteri, Ildiko; Strobl, Birgit; Müller, Mathias; Kalinke, Ulrich; Merad, Miriam; Knapp, Sylvia
Abstract : Upon infection, alveolar macrophages encounter and ingest Streptococcus pneumoniae to then induce an inflammatory response that involves secretion of IFN‐I. In a similar manner, sterile acute lung injury is associated with tissue damage and resulting inflammation. Respiratory epithelial cells are damaged in the course of pulmonary inflammation, which is diminished in the presence of IFN‐I, which directly protects alveolar epithelial type II cells from death. Abstract : Protecting the integrity of the lung epithelial barrier is essential to ensure respiration and proper oxygenation in patients suffering from various types of lung inflammation. Type I interferon (IFN‐I) has been associated with pulmonary epithelial barrier function, however, the mechanisms and involved cell types remain unknown. We aimed to investigate the importance of IFN‐I with respect to its epithelial barrier strengthening function to better understand immune‐modulating effects in the lung with potential medical implications. Using a mouse model of pneumococcal pneumonia, we revealed that IFN‐I selectively protects alveolar epithelial type II cells (AECII) from inflammation‐induced cell death. Mechanistically, signaling via the IFN‐I receptor on AECII is sufficient to promote AECII survival. The net effects of IFN‐I are barrier protection, together with diminished tissue damage, inflammation, and bacterial loads. Importantly, we found that the protective role of IFN‐I can also apply to sterile acute lung injury, in which loss of IFN‐I signaling leads to a significant reduction in barrier function caused by AECII cell death. Our data suggest that IFN‐I is an important mediator in lung inflammation that plays a protective role by antagonizing inflammation‐associated cell obstruction, thereby strengthening the integrity of the epithelial barrier.